Development of ciprofloxacin resistance due to chromosomal mutations induced by 2-nitrofluorene - Birošová, Lucia; Mikulášová, Mária (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
In this paper we investigated the ability of 2-nitrofluorene to induce mutations leading to antibiotic resistance in quinolone-sensitive strain Salmonella typhimurium. After preincubation of bacteria with 2-nitrofluorene, the frequency of mutation to ciprofloxacin resistance was 57 fold higher than in the case of spontaneous mutability. Some of resultant resistant colonies showed a great increase of ciprofloxacin MIC.
Keywords: mutace; bakteriální geny; ciprofloxacin; Genes, Bacterial; Salmonella typhimurium; antiinfekční látky; Anti-Infective Agents; Ciprofloxacin; Drug Resistance, Bacterial; Mutation; fluoreny; bakteriální léková rezistence; Fluorenes